2012
DOI: 10.4028/www.scientific.net/amm.236-237.1156
|View full text |Cite
|
Sign up to set email alerts
|

SVM Based Land/Sea Clutter Classification Algorithm

Abstract: In this paper, a support vector machine (SVM) based land/sea clutter classification algorithm was proposed. For target location error correction based on passive beacon reference source of over-the-horizon radar (OTHR), the signal model of land/sea clutter is established, the three kinds of multi-features of land/sea clutter are analyzed, and the classification algorithm based on SVM using multi-features is detailed. Simulation experiments were carried out for different clutter-noise- ratios, and the results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Therefore, identification and localization of clutter and interference regions in the RD spectrum is the first step. Conventional detection of clutter or interference regions is achieved by image segmentation or classifier classification [18][19][20], and detection performance depends on many artificial factors. However, the deep-learning-based Faster R-CNN detection framework [21], which can simultaneously localize and classify the target in less time through learning, has a good detection effect on normal-sized targets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, identification and localization of clutter and interference regions in the RD spectrum is the first step. Conventional detection of clutter or interference regions is achieved by image segmentation or classifier classification [18][19][20], and detection performance depends on many artificial factors. However, the deep-learning-based Faster R-CNN detection framework [21], which can simultaneously localize and classify the target in less time through learning, has a good detection effect on normal-sized targets.…”
Section: Introductionmentioning
confidence: 99%
“…This method overcomes the inaccuracy caused by subjective selection of α and implements the algorithm's self‐adaptation to clutter environment. Jin Zhenlu and others [5] proposed a multi‐feature recognition algorithm for land/sea clutter based on support vector machine (SVM). The land/sea clutter echo signal model was established by using SVM to improve the land/sea clutter recognition rate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the algorithms in literature [3] and literature [4] have the disadvantages of a complex model and a large amount of computation. In the literature [5] and literature [6], the application of SVM in radar clutter recognition has the disadvantages of low recognition accuracy and long training time.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the backscatter coefficient of topographic features and the sea have been investigated as a way to improve the geolocation accuracy of targets via a process known as coordinate registration. This is the process of transforming from the radar (or group) range to the ground range to obtain the geographic coordinates of an object observed by a radar [15]- [18]. It has been found that the difference in the backscatter coefficient of certain topographic features could be suitable for coordinate registration.…”
mentioning
confidence: 99%